PENGARUH PENERAPAN TEKNIK SPOTLIGHT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 4 MUARA BUNGO - Sari, Rina Busrina; Aima, Zulfitri; Harisman, Yulyanti (STKIP PGRI Sumbar, 2013)
Background of this research is comprehension of concept studied mathematic at studentÂ SMPN 4 Muara Bungo class VIII is still low. The purpose of this research is to know what is studied comprehension of concept studentÂ with spotlight technique is good than conventional study at SMPN 4 Muara Bungo class VIII. Kinds of this research is experimental research with hypothesis p-value is 0,005, so hypothesis is receive. So that can concluded that comprehension of concept with spotlight technique Â is good than comprehension of concept with conventional study at SMPN 4 class VIII Muara Bungo